Entrepreneurial Management as a Predictor of Business Performance in the Greater Accra Region, Ghana - Nicholas Kofi Nti (Journal of Management and Entrepreneurship Research, 2022)
Objective: This study used the Behavioural theory of entrepreneurship as the theoretical foundation, and correlation research design to examine the impact of the entrepreneurial management practices (strategic orientation, resource orientation, management structure, reward philosophy, growth orientation, and entrepreneurial culture) on business performance in Ghana. Research Design & Methods: 500 businesses in the Greater Accra Region were selected for the data analysis. Descriptive statistics and hierarchical multiple regression were used to analyse the data. Findings: After controlling the business profile, the result showed that four out of the six entrepreneurial management practices – resource orientation, strategic orientation, reward philosophy, and entrepreneurial culture significantly predicted business performance. However, growth orientation and management structure did not. Implications & Recommendations: The study concludes that entrepreneurial management practices improve business performance in Ghana. The researcher recommends that approaching the study with a mixed-method will help provide a holistic understanding of the management decision-making of the entrepreneurs and its impact on their business performance. Contribution & Value Added: This study contributes to the entrepreneurial management literature in Ghana.